Moderate to vigorous physical activity volume is an important factor for managing nonalcoholic fatty liver disease: A retrospective study - Oh, Sechang; Shida, Takashi; Yamagishi, Kazumasa; Tanaka, Kiyoji; So, Rina; Tsujimoto, Takehiko; Shoda, Junichi (Hepatology (Baltimore, Md.), 2015)
Recently, the beneficial effects of increased physical activity (PA) on nonalcoholic fatty liver disease (NAFLD) in obese subjects were reported. However, the optimal strength and volume of PA in lifestyle modification to improve NAFLD pathophysiology and be recommended as an appropriate management of this condition are unclear. The primary goal of this retrospective study was to estimate the beneficial effects of a varying volume of moderate to vigorous intensity PA (MVPA) on the improvement of NAFLD. A total of 169 obese, middle‐aged men were enrolled in a 12‐week weight reduction program through lifestyle modification consisting of dietary restrictions plus aerobic exercise. Among these obese subjects, 40 performed MVPA for <150 min·wk−1, 42 performed MVPA for 150‐250 min·wk−1, and 87 performed MVPA for >250 min·wk−1. The subjects in the MVPA ≥250 min·wk−1 group, in comparison with those in the MVPA <250 min·wk−1 group, showed significantly attenuated levels of hepatic steatosis (−31.8% versus −23.2%). This attenuation was likely independent of the detectable weight reduction. MVPA for ≥250 min·wk−1 in comparison with that for <150 min·wk−1 led to a significant decrease in the abdominal visceral adipose tissue severity (−40.6% versus −12.9%), levels of ferritin (−13.6% versus +1.5%), and lipid peroxidation (−15.1% versus −2.8%), and a significant increase in the adiponectin levels (+17.1% versus +5.6%). In association with these changes, the gene expression levels of sterol regulatory element‐binding protein‐1c and carnitine palmitoyltransferase‐1 in peripheral blood mononuclear cells also significantly decreased and increased, respectively. Conclusion: MVPA for ≥250 min·wk−1 as part of lifestyle management improves NAFLD pathophysiology in obese men. The benefits seem to be acquired through reducing inflammation and oxidative stress levels and altering fatty acid metabolism. (Hepatology 2015;61:1205–1215)